Neutrophilic inflammation in bronchiectasis - James D. Chalmers; Mark Metersky; Stefano Aliberti; Lucy Morgan; Sebastian Fucile; Melanie Lauterio; Patrick P. McDonald (European Respiratory Review, 2025)
Noncystic fibrosis bronchiectasis, hereafter referred to as bronchiectasis, is a chronic, progressive lung disease that can affect people of all ages. Patients with clinically significant bronchiectasis have chronic cough and sputum production, as well as recurrent respiratory infections, fatigue and impaired health-related quality of life. The pathophysiology of bronchiectasis has been described as a vicious vortex of chronic inflammation, recurring airway infection, impaired mucociliary clearance and progressive lung damage that promotes the development and progression of the disease. This review describes the pivotal role of neutrophil-driven inflammation in the pathogenesis and progression of bronchiectasis. Delayed neutrophil apoptosis and increased necrosis enhance dysregulated inflammation in bronchiectasis and failure to resolve this contributes to chronic, sustained inflammation. The excessive release of neutrophil serine proteases, such as neutrophil elastase, cathepsin G and proteinase 3, promotes a protease–antiprotease imbalance that correlates with increased inflammation in bronchiectasis and contributes to disease progression. While there are currently no licensed therapies to treat bronchiectasis, this review will explore the evolving evidence for neutrophilic inflammation as a novel treatment target with meaningful clinical benefits.